Effect of social Media on mental health - Islam, Tahshinul; Farhan, Tajish; Ahmed Turjo, Syed Thakdir; Pretty, Nusrat Jaman; Sababa, Tasfia Haque (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.